SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JURUSAN PADA SMK NEGERI 1 PURWOSARI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Istikhomah, Istikhomah; Sujito, Sujito; Widayanti, Rahayu (DINAMIKA DOTCOM, 2016)
Efforts to improve the quality of education in Indonesia has always received attention from various parties. One of the components that also affect educational change is the selection of majors. Selection of majors usually done when the learners (students) enter upper secondary education either SMA / MA and SMK. Selection of department at SMK Negeri 1 Purwosari done at the beginning of the new school year.Making the decision support system aims to simplify the committee PSB in the calculation. Methods in making this system using Simple Additive weighting which is one method of Multi-Attribute Decision Making (MADM) with a value criterion psychological tests, medical tests, interview English, written tests, math scores, the value of science, the value of Indonesian and value Language Britain from the previous school.Based on the results of testing the quality of the system is obtained an average value of 3.91 which shows the system in both categories, thus helping the committee PSB in determining the direction according to their talents and interests of students.Keyword: Elections Department , Simple Additive weighting , Decision Support System